A green methodology for C–S cross-coupling reaction over CuII attached to magnetic natural talc (γ-Fe2O3/talc/CuII NPs) as a heterogeneous and ligand-free catalyst. (2nd January 2023) - Nayamadi Mahmoodabadi, Malihe; Akhlaghinia, Batool
Abstract: Herein a prominent, efficient, facile and environmentally benign catalytic activity of γ-Fe2 O3 /talc/Cu II NPs (as a superparamagnetic composite with average diameter of about 20-30 nm) has been shown in C–S cross-coupling reactions. A wide variety of aryl iodides, aryl bromides and aryl chlorides with electron-donating or electron-withdrawing substituents reacted with S8 or thiourea forming the corresponding substituted diphenyl sulfides under eco-friendly and mild process conditions. The results demonstrated remarkable catalytic activity of the nanostructured catalyst such as chemoselectivity and functional group tolerance. γ-Fe2 O3 /talc/Cu II NPs as a magnetic catalyst was stable under reaction conditions and can be recycled at least five times with minimal loss of catalytic activity. Moreover, the use of commercially available and chemically stable sulfur transfer agent, eco-friendly and low-cost solvent and base as well as operational simplicity and easier work-up procedure make this method a promising candidate for potential applications in some organic reactions. GRAPHICAL ABSTRACT: UF0001